Microfinance as a tool for socio-economic empowerment of rural women in Northern Malawi : a practical theological reflection - Chilongozi, Mwawi Nyirenda (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.